Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Review Exercises - Page 173: 27



Work Step by Step

$(f+g)(x)=f(x)+g(x)$ $(f+g)(x)=f(x)+g(x)=x^2-2x+x-5=x^2-x-5$ Plug in $x=-2$ into $(f+g)(x)$: $(f+g)(-2)=(-2)^2-(-2)-5=4+2-5=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.